Post-urban spaces in contemporary irish fiction : transcultural spaces and places. - Barros-Grela, Eduardo (1974-....); Barros-Grela, Eduardo (1974-....); Clark, David (1956-....); Clark, David (1956-....) (TIR (Travaux d'Investigation et de Recherche), 2023)
The emergence of spatial experience has sparked a notable interest within the realm of critical theory, leading to a comprehensive exploration and conceptualization of various cultural, ideological, and aesthetic movements that have emerged from the discourse on space. This intellectual pursuit has given rise to a multitude of studies examining diverse artistic representations of space, and these studies explore the distinct characteristics inherent to each geographical and cultural context, in the case of this collection, Ireland. Through their varied approaches and analyses, these studies have revitalized human beings' relationships with spaces, while also acknowledging the marginalized perception of overlooked places that are in need of recognition. Thus, "Post-Urban Spaces in Contemporary Irish Fiction, Transcultural Spaces and Places" assembles a range of diverse perspectives that delve into the reconfiguration of spaces within contemporary Irish aesthetics. In line with the broader field of Space Studies, this volume encompasses essays that explore the intersection of Irish spaces with other areas of knowledge and theoretical approaches. Eduardo Barros Grela is Senior Lecturer at the Universidade da Coruña and Coordinator of the Research Group "Irish Studies". David Clark is Senior Lecturer at the Universidade da Coruña and Director of the "Amergin" University Institute of Research in Irish Studies.